Proceedings of the State-level Consultation Workshop on Policy Coherence in the Food, Land, and Water Systems: Case Study of Odisha, India, Odisha, India, 14 December 2023 - Taneja, Garima; Negi, U.; Shukla, S.; Joshi, T.; Neog, K.; Katyaini, S.; Mitra, Archisman; Bhattacharjee, Suchiradipta; Bassi, N.; Verma, Shilp (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2023)
International Water Management Institute (IWMI) and the Council on Energy, Environment and Water (CEEW) organized a state consultation workshop on 14 December 2023 on ‘Policy Coherence in Food, Land, and Water (FLW) Systems: A case study of Odisha’ at Bhubaneswar as a part of the CGIAR Initiative on National Policies and Strategies Initiatives (NPS). The Food, Land and Water (FLW) project aims to identify key state-level policies in the food, land, and water systems that have a practical scope for improving coherence and hold most potential for creating an impact. The workshop was organized in partnership with the Department of Agriculture and Farmers’ Empowerment, Government of Odisha.